ISOLATION AND IDENTIFICATION OF ALLELOPATHIC COMPOUNDS FROM THE RESIDUES OF SOME SUNFLOWER CULTIVARS USING HPLC TECHNOLOGY - Alaa A. J. AL-Behadili, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This research was conducted to detect some of the allelopathic chemical class in plant residues of nine cultivars of sunflower, including Zahret Al-Iraq, Luleo, Turkie, Al-Isaqi 1, Al-Isaqi 2, Tarzan, Akmar, Shumoos, and Sin Al-Theeb, using appropriate chemical reagents. Some of these chemical were furthered analysed  for their content of allelopathic comopounds using High-Performance Liquid Chromatography (HPLC). Results revealed the presence of glycosides, alkaloids, tannins, terpenes, steroids and flavonoids the plant residues of the test sunflower cultivars. Concentrations of glycosides, tannins, alkaloids, and flavonoids were measured, were found to be highter in Shumoos and Tarzan 1018 cultivar residues. The analysis with the High-Performance Liquid Chromatography (HPLC) indicated the presence of several allelopathic compounds of phenolic in nature in the different sunflower cultivar residues, namely Rutin, Vanillin, Resorcinol, and Quercetin.